Stock portfolio hedging with financial options - Juan Andrés Jaramillo-Restrepo; Miguel Jiménez-Gómez; Natalia Acevedo-Prins (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The financial market currently offers derivative products whose characteristics allow investors to reduce the negative impact of natural market fluctuations on the value of their assets. Hedging with financial options is one of the possible strategies that an investor can implement in order to reduce the exposure or risk of their investments. This paper aims to assess the real impact of financial options as a hedging instrument on an investment portfolio made up of variable income assets of the Colombian market. The results show that for options with an upward trend, call options allow future losses to be hedged; on the other hand, for bearish trends, coverage is made with put options.